Microbial Communities in North American Ixodid Ticks of Veterinary and Medical Importance - Varela-Stokes, Andrea S.; Park, Si Hong; Kim, Sun Ae; Ricke, Steven C. (Frontiers in Veterinary Science, 2017)
Interest in microbial communities, or microbiota, of blood-feeding arthropods such as ticks (order Parasitiformes, suborder Ixodida) is increasing. Studies on tick microorganisms historically emphasized pathogens of high medical or veterinary importance. Current techniques allow for simultaneous detection of pathogens of interest, non-pathogenic symbionts, like Coxiella-LE and Francisella-LE, and microorganisms of unknown pathogenic potential. While each generation of ticks begins with a maternally-acquired repertoire of microorganisms, microhabitats off and on vertebrate hosts can alter the microbiome during the life cycle. Further, blood-feeding may allow for horizontal exchange of various pathogenic microbiota that may or may not also be capable of vertical transmission. Thus, the tick microbiome may be in constant flux. The geographical spread of tick vector populations has resulted in a broader appreciation of tick-borne diseases and tick-associated microorganisms. Over the last decade, next-generation sequencing technology targeting the 16S rRNA gene led to documented snapshots of bacterial communities among life stages of laboratory and field-collected ticks, ticks in various feeding states, and tick tissues. Characterizing tick bacterial communities at population and individual tissue levels may lead to identification of markers for pathogen maintenance, and thus, indicators of disease “potential” rather than disease state. Defining the role of microbiota within the tick may lead to novel control measures targeting tick-bacterial interactions. Here we review our current understanding of microbial communities for some vectors in the family Ixodidae (hard ticks) in North America, and interpret published findings for audiences in veterinary and medical fields with an appreciation of tick-borne disease.